Abundance and Characteristics of Fibrous Microplastics and Microfibers Isolated in Mullus barbatus from the Adriatic Sea—Preliminary Investigation - Serena Santonicola; Michela Volgare; Mariacristina Cocca; Giampaolo Colavita (Microplastics, 2023)
Despite the wide distribution of textile microfibers in the marine environment, there is still limited knowledge on microfiber ingestion in fish species intended for human consumption, mostly due to analytical issues. The present study aims to assess the occurrence of microfibers in red mullet (Mullus barbatus) samples collected from the Italian waters of the central Adriatic Sea. M. barbatus is a bottom fish that lives in contact with sediment and therefore was proposed as a sentinel species for the monitoring plastic pollution. A visual approach based on the evaluation of specific microfiber surface morphology was applied for the identification of particles of different origins. The preliminary findings showed the presence of microfibers in 80% of red mullet samples with a mean of 5.95 microfibers/individual. The majority (>80%) of the isolated microfibers were of natural/artificial origin, while the dominant colors were blue and black. The obtained results confirmed that benthic fish species are susceptible to microfiber ingestion and indicate the high availability of these particles in the Adriatic basin. Considering the spectroscopic drawbacks in microfiber analyses and the need to improve the current knowledge on the rate of contamination of fishery products, the visual approach could be a feasible, easy, and accessible method in the study of microfiber pollution, and the assessment of consumer health risks.